Knowledge, Practice and Perceived Threat toward Breast Cancer in the Women living in Gorgan, Iran - Abdolrahman Charkazi; Arazbordi Ghourchaei; Atena RazzaqNejad (Golestan University of Medical Sciences, 2013)
Background and Objective: Breast cancer is the most frequent cancer among women worldwide. The objective of the current study was to assess the breast cancer screening behaviors adherence rate and its relation with perceived susceptibility and perceived severity in Gorgan, Iran.   Material and Methods: In a cross sectional study, 300 women referring to two health centers were selected through cluster sampling .Data gathering instrument was a questionnaire including demographic, knowledge and practice questions related to breast cancer screening behaviors. Perceived susceptibility and perceived severity measured by Champion's Health Belief Model Scale .   Results: The subjects are 18 to 60 years (30.3 ± 7.3). In knowledge part, 88.3% could not answer any question. In practice section, they have breast self examination (33%), clinical breast examination (11.3%) and mammography (5%) in their past history. Four- point -seven percent have high level of susceptibility and 46.7% high level of severity. Higher susceptibility was significantly associated with mammography (p=0.042) performance and not associated with breast self examination and clinical breast examination.   Conclusion: The participant's knowledge about breast cancer screening was inappropriate. Meanwhile, the majority of them have low level of perceived susceptibility. It is a necessity to improve the knowledge and perceived susceptibility for enhancing the breast cancer screening behaviors.